Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L (Tree Physiology, 2004)
Photoinhibition was examined in four co-occurring Mediterranean evergreen tree species during two consecutive winters. In response to low temperatures and saturating light, Juniperus phoenicea L., Pinus halepensis Mill., Quercus coccifera L. and Q. ilex ssp. ballota (Desf.) Samp. exhibited marked chronic photoinhibition, indicated by low predawn maximal photochemical efficiency of photosystem II (PSII) (Fv/Fm). Low Fv/Fm values were correlated with high concentrations of xanthophyll cycle components (VAZ) and with the maintenance of high concentrations of zeaxanthin overnight (DPSpd). In all species, however, chronic photoinhibition was enhanced as the winter progressed in the absence of changes in DPSpd, suggesting cumulative damage toward the end of winter.Photoinhibition differed among species: P. halepensis always displayed significantly higher Fv/Fm values; and Q. coccifera had the lowest Fv/Fm values, showing a high sensitivity to the combination of high light and low temperatures. Differences among species were not fully explained by differences in the xanthophyll pool or its de-epoxidation state. Chronic photoinhibition overlapped with a dynamic photoinhibition as shown by the low values of photochemical efficiency of the open reaction centers of PSII at midday. Winter photoprotective strategies differed among species and may involve photoprotective mechanisms in addition to those associated with xanthophylls. The observed species-specific differences matched results obtained for the same species in summer; however, comparison of the two seasons suggests that the higher VAZ concentration observed in winter has an additional structural photoprotective role.
From Duplicate 2 (Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L)
Keywords: chlorophyll; Chlorophyll: physiology; Juniperus; Juniperus: physiology; photoprotection; Pinus; Pinus: physiology; Plant Leaves; Plant Leaves: physiology; Quercus; Quercus: physiology; Seasons; Sunlight; Trees; Trees: physiology; xanthophyll cycle